Who Studies MOOCs? Interdisciplinarity in MOOC Research and its Changes over Time - Veletsianos, George; Shepherdson, Peter (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2015)
The complexity of digital and online education is becoming increasingly evident in the context of research into networked learning/participation. Interdisciplinary research is often proposed as a way to address complex scientific problems and enable researchers to bring novel perspectives into a field other than their own. The degree to which research on Massive Open Online Courses (MOOCs) is interdisciplinary is unknown. We apply descriptive and inferential statistics to bibliometric data to investigate interdisciplinarity in MOOC research. Results show that MOOC research published in 2013-2015 was (a) mostly conducted by researchers affiliated with Education and Computer Science disciplines, (b) far from monolithic, (c) had a greater representation of authors from Computer Science than in the past, and (d) showed a trend toward being more interdisciplinary than MOOC research published in 2008-2012. Our results also suggest that empirical research on xMOOCs may be more interdisciplinary than research on cMOOCs. Greater interdisciplinarity in xMOOC research could reflect the burgeoning interest in the field, the general familiarity with the xMOOC pedagogical model, and the hype experienced by xMOOCs. Greater interdisciplinarity in the field may also provide researchers with rich opportunities to improve our understanding and practice of digital and online learning.